The impact of the lockdown by COVID-19 on Temporomandibular Disorder related pain intensity, distress and post-traumatic stress disorder - A case-control study (Research, Society and Development, 2022)
The events related to the COVID-19 pandemic are having a strong impact on public mental health. However, there are few studies focusing on these aspects in patients with temporomandibular disorders (TMD). The aim of this study was to evaluate the painful intensity, distress and symptoms of post-traumatic stress disorder (PTSD) in a population with and without TMD during the COVID-19 pandemic. This case-control study evaluated electronic questionnaires from 197 participants (105 with TMD and 92 controls), that were carried out during and after the first lockdown due to COVID-19 pandemic. To assess the presence of possible TMD, painful intensity, distress, and PTSD symptoms the respective questionnaires were used: TMD Pain Screener, Numeric Rating Scale, Patient Health Questionnaire – 4 and PTSD Checklist - Civilian Version. TMD participants showed higher levels of distress during (p = 0.027) and after (p < 0.001) the lockdown compared to the control group. The TMD group also reported increased levels of distress in the post-lockdown period in relation to the period during the lockdown (p = 0.002), although the same intensity of pain was observed at both evaluated periods. Furthermore, participants with TMD were 3.91 × more likely to be female (CI 95% = 1.88-8.13) and 3.82 × more likely to show PTSD symptoms (CI95% = 1.61-9.08) after the lockdown. These data suggest that a pre-existing painful condition can lead to increased distress and symptoms of PTSD as a result of stressful situations, such as the COVID-19 pandemic lockdown.